Pengembangan Website Marketplace Binatang Peliharaan dengan Fitur Lelang Menggunakan Metode Rapid Application Development - Raymond Sutjiadi; Titasari Rahmawati; Edbertinus Halim (Universitas Diponegoro, 2021)
Through marketplace website, someone can open a business using relatively low capital without the need to open physical store. The benefit using marketplace website is wider market range so that able to get customers easily. On the other hand, pet lovers often feel difficulties to buy a pet. Moreover, rare pets are traded using higher bargaining price between sellers and buyers. This causes difficulties to find mutually beneficial price on both sides. In this research is developed marketplace website to sell pets, which is equipped with auction feature. Via this auction feature will facilitate sellers and buyers to find beneficial dealling price. This website is developed using Rapid Application Development method which prioritizes the speed of application development. The features of this marketplace website are depicted using Unified Modelling Language (UML). From the testing result, it can be seen that buying and selling features can simplify sellers to market their products. Auction feature also can run automatically on certain determined deadline to find best bidding price from buyer